Pengaruh Komitmen Organisasi dan Disiplin Kerja Terhadap Kinerja Pegawai Pada Kantor Kecamatan Walantaka Kota Serang - Salapudin; Pramudi Harsono; Risma Eka Desiyani (Fakultas Ekonomi dan Bisnis Universitas Prima Graha, 2021)
This study aims to determine: The Effect of Organizational Commitment on Employee Performance. The Effect of Work Discipline on Employee Performance. The Effect of Organizational Commitment and Work Discipline on Employee Performance at the Walantaka District Office, Serang City. The type method in this study uses an associative quantitative method that is causal, which is a study to determine the relationship/influence of the independent variable on the dependent variable without making additional changes or manipulation of existing data. The population and samples used in this study were employees at the Walantaka District Office, Serang City, amounting to 32 employees. The sampling technique in this study uses a saturated sample where the population is less than <100 employees. The results of this study indicate that: There is a positive and significant effect of Organizational Commitment on Employee Performance. There is a positive and significant effect of Work Discipline on Employee Performance. There is a positive and significant effect of Organizational Commitment and Work Discipline together on Employee Performance at the Walantaka District Office, Serang City.